2012
DOI: 10.3122/jabfm.2012.05.120178
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Research Conducted in Networks: Getting Down to Business

Abstract: This seventh annual practice-based research theme issue of the Journal of the American Board of Family Medicine highlights primary care research conducted in practice-based research networks (PBRNs). The issue includes discussion of (1) theoretical and methodological research, (2) health care research (studies addressing primary care processes), (3) clinical research (studies addressing the impact of primary care on patients), and (4) health systems research (studies of health system issues impacting primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Research further showed that there is little interest in research among many GPs, because they perceive little relevance and were not involved in the study design [ 6 , 7 ]. In some countries, practice networks for research in primary care have been established to facilitate scientific research in ambulatory care settings [ 8 ]. In Germany, some research networks for primary care research have been initiated as well, but most are at an early stage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research further showed that there is little interest in research among many GPs, because they perceive little relevance and were not involved in the study design [ 6 , 7 ]. In some countries, practice networks for research in primary care have been established to facilitate scientific research in ambulatory care settings [ 8 ]. In Germany, some research networks for primary care research have been initiated as well, but most are at an early stage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This requires research into interventions that are specifically delivered in the community and, as such, a research priority is recruitment in a general practice setting. This has been recognised by the development of practice-based research networks internationally [1012].…”
Section: Introductionmentioning
confidence: 99%
“…A robust evidence base of treatment effectiveness for people in the community is therefore required. As such, a research priority is recruitment in a general practice setting as recognised by the development of practice-based research networks internationally [19][20][21]. For this review's purpose, both recruiters and participants are included.…”
Section: Introductionmentioning
confidence: 99%